PENGARUH PROFITABILITAS, KESEMPATAN INVESTASI DAN LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN - admin, YUVENSIA B11111064 (Jurnal Manajemen Update, 2016)
This research aims to analyze the influence of profitability, invesment opportunity set and liquidity of the dividend dplicy (DPR) in LQ45 companies which are listed in Indonesian Stock Exchange in the year 2010 until 2013. This research uses secondary data which was used in the form of financial statements  samples obtained from the IDX. This research used purposive sampling, data collection have been done by specifying the criteria for determining sampel resulting in 16  LQ45 companies during the 4 years of observation. The hypotheses were tested using multiple linear regression analysis model. Based on the results of studies using  multiple linear regression analysis model  showed that the profitability and liquidity has  positive affect on the dividend policy (DPR), but the investment opportunity has a positve significant influence on the dividend policy (DPR). Third independent variables just can explain dividend payout ratio of 18%. Key words: dividend policy (DPR) , profitability (ROE), investment opportunity set and liquidity (CR).